Optimization of aerodynamic stability in ski jumping: The tug-of-the-war between safety and performance - Marques-Bruna, P.; Grimshaw, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Past research in ski jumping has aimed to increase jump length and modify ski length and hill design to make the sport safer (Schwameder, 2008). However, the assessment of aerodynamic stability (Anderson, 2007) for improved safety has received less attention (Seo et al., 2004). Thus, this study aimed to model aerodynamic efficiency and stability in pitch in ski jumping as a function of athlete`s posture. The findings may be used to optimise flight posture and warrant safer training and competition. Methods: Mathematical modelling was carried out using a hypothetical ski jumper with a typical mass of 70 kg, height of 1.76 m and ski length of 2.57 m (Seo et al., 2004). Lift (FL), drag (FD), lift/drag ratio (FL/FD), dPitching-moment/dAngle-of-attack slope (dM/dAA) at the trim AA and oscillatory frequency (FREQ) (Anderson, 2007) were calculated as a function of AA, ski opening angle (SOA; at 20°, 25° and 30°) and forward-leaning angle (FLA; at 0°, 10°, 20°, 30° and 40°) (Seo et al., 2004). Air density was set at 1.18 kg/m3, and air speed at 25 m/s to simulate competition at a large jumping hill (Schwameder, 2008). Results: FL was largest with SOA = 30° & FLA = 0°-10°. FD increased monotonically from AA = 10°. FL/FD peaked at AA = 2°-12°, at which FL was rather low. dM/dAA became steeper with increased SOA and FLA, ranging from - 0.82 Nm/° for SOA = 20° & FLA = 0° to - 2.67 Nm/° for SOA = 30° & FLA = 40°. FREQ increased as a function of SOA and FLA, showing about half a cycle per second (0.51 Hz) for SOA = 30° & FLA = 10°. Discussion/Conclusion: An optimised flight posture of SOA = 30° & FLA = 10° is suggested. This is a high-lift configuration that yields steep dM/dAA and high oscillatory frequency upon sudden deviations from trimmed flight. The high frequency may initiate transitory dynamic oscillations (Anderson, 2007). The findings add to the current priority to warrant safety in the sport (Schwameder, 2008).